Identification of suitable housekeeping genes for normalization of quantitative real‐time PCR data during different physiological stages of mammary gland in riverine buffaloes (Bubalus bubalis). Issue 6 (30th January 2013) - Aggarwal, J.; Sharma, A.; Kishore, A.; Mishra, B. P.; Yadav, A.; Mohanty, A.; Sodhi, M.; Kataria, R. S.; Malakar, D.; Mukesh, M.
Summary Gene expression analysis unravels the complex changes or relations at transcriptomic level. To nullify all type of errors that can be incorporated during any stage of RNA extraction into cDNA synthesis and for reliable results, the data obtained from qPCR have to be normalized using the appropriate/suitable housekeeping genes (HKGs). Unfortunately, till date, no such HKG has been reported for bubaline mammary gland. The objective of the present study was thus to identify and validate the potential HKGs for the gene expression studies in buffalo mammary gland. Mammary tissues from twelve buffaloes during different physiological stages: pre‐pubertal (heifer), lactation and involution were obtained for the present study. A total of 16 potential HKGs (GAPDH, β‐actin, UXT, β2M, A2M, RPl4, RPS9, RPS15A, RPS18, RPS23, HMBS, HPRT1, GTP, EEF1A1, UB1 and RPL22) from different functional classes were evaluated. The analysis revealed that the expression of EEF1A1, RPl4, β2M and RPS15A was most consistent across different physiological stages of buffalo mammary gland. On the other hand, β‐actin, A2M, RPL22 and GAPDH were the least stable genes making them unsuitable as HKGs. Based on our analysis, we recommend the use of EEF1A1, RPl4, β2M and RPS15A genes as suitable HKGs for accurate normalization of gene expression data in bubaline mammary gland.